FAKTOR-FAKTOR YANG MEMPENGARUHI PERUBAHAN PENUTUPAN LAHAN DI DALAM KAWASAN HUTAN LINDUNG GUNUNG SIRIMAU - Tuakora, Marleen Annette; Mardiatmoko, Gun; Lelloltery, Henderina (MAKILA, 2022)
This study aims to know about the factors that influenced land cover changes in Gunung Sirimau Protected Forest Area. The method used in this study is crosstab analysis with a chi-square test, which is used to know the correlation between one variable and another variable. This study showed that people's dependence on forests influenced the land cover change in the Gunung Sirimau Protected Forest area. At the same time, other factors such as the income of people, knowledge about forest boundaries, and natural disasters did not influence land cover change in Gunung Sirimau's protected forest.